Knowledge, Attitude and Practice Regarding Breast Self Examination Among Female Health Personnel - Shrestha Pradhan, Santoshi; Shrestha, Roshanee; Parajuli, Puspa; Khagi, Rana B; Bhandari, Buna (Journal of Kathmandu Medical College, 2018)
Background: The knowledge, attitude and practice of Breast Self Examination is an important method of prevention of breast cancer which helps to detect the changes in early stage and delay seeking medical care. So female’s knowledge, attitude and practice of Breast Self-Examination play a crucial role in the safeguard of their health. Objectives: To assess the knowledge, attitude and practice regarding Breast Self Examination among female health personnel working in Kathmandu Medical College and Teaching Hospital. Methodology: A cross-sectional study was conducted among 320 female health personnel to assess the knowledge, attitude and practice regarding Breast Self-Examination working in Kathmandu Medical College and Teaching Hospital using self administered structured questionnaire. Descriptive and inferential statistics was used to analyze the data using SPSS 16 Version. Results: The findings revealed that the majority 232 (72.5%) of the respondents had average level of knowledge, 70 (21.9%) had poor level of knowledge and only 18 (5.6%) had good level of knowledge respectively. On the other hand, majority of the respondents 304 (95%) had good attitude whereas only 16 (5.0%) had poor attitude regarding Breast Self Examination. There was statistically significant association between knowledge and age, ethnicity and marital status (p=<0.05). Attitude was associated with age, religion, profession and level of education (P=<0.05). There was very weak correlation (r=0.094) between knowledge and attitude. Conclusion: The study concluded that there was average level of knowledge regarding Breast Self Examination. Female’s attitude towards Breast Self-Examination was positive though the practice was poor. Breast Self Examination is one of the most important techniques for screening and diagnosis in early stages. Therefore, the study highlights the need for educational programs to create awareness regarding Breast Self-Examination. Journal of Kathmandu Medical College, Vol. 6, No. 4, Issue 22, Oct.-Dec., 2017 Page: 156-160